Perceptions of Innovation Characteristics Converter Kit Engine and Its Influence on Fishermen's Income in Palembang City - Shelia Shelia; Sriati Sriati; Indah Widiastuti (Journal of Global Sustainable Agriculture, 2023)
The oil-to-gas fuel conversion program is an energy diversification policy carried out by the government to reduce fishing communities' dependence on oil fuel by assisting in the form of converter kit engines. The converter kit engine innovation is believed to be more efficient and effective than the ordinary boat propulsion engines previously used by fishermen. This research aims to identify the socio-economic characteristics of fishermen, analyze fishermen's perceptions of the characteristics of converter kit engine innovation, and analyze the relationship between perceptions and fishermen's income. The method in this research is a survey method. The research subjects consisted of 51 fishermen who received converter kit engines. Data was collected using a questionnaire designed using a Likert scale. The research results showed that the achievement value of fishermen's perception of the characteristics of converter kit engine innovation was 92.03% and was classified as very high. The correlation test results between the variables of fishermen's perceptions of the innovative characteristics of converter kit engines and fishermen's income have a fragile and insignificant relationship with a negative correlation coefficient or in the opposite direction of -0.185.